Multi-material 3D printed PLA/PA6-TiO2 composite matrix: rheological, thermal, tensile, morphological and 4D capabilities. Issue 2 (3rd April 2022) - Kumar, Sudhir; Singh, Rupinder; Singh, Mohit
ABSTRACT: The flexibility provided by fused deposition modelling (FDM) in processing of thermoplastic composite matrix (polylactic acid (PLA), polyamide6 (PA6) etc.) has made this process acceptable in different fields of research varying from structural, non-structural engineering, medicinal and space applications. But hitherto little has been reported on multi-material printing of PLA/PA6-TiO2 (70–30 wt %) matrix composite on FDM for biomedical scaffolding applications. In this work, the biocompatible grade of PLA, PA6-TiO2 (70–30 wt %) has been selected. An effort has been made for multi-material printing of PLA/PA6-TiO2 polymeric matrix and optimised printing conditions for FDM processing of selected layer combinations were ascertained. The results of mechanical testing suggest that, Infill speed: 90mm/s, Infill pattern: rectilinear and layer combination: PLA 5 layers/PA6-TiO2 5 layers are the optimised conditions for the FDM processing. From thermal analysis, it has been observed that both PLA and PA6-TiO2 are thermally stable. Finally, PLA/PA6-TiO2 based prototypes have shown controlled two-way 4D capabilities under the hot (70°C) and cold (10°C) water (selected as stimulus in present case). The results of mechanical testing have been supported by morphological analysis (surface porosity) on fractured surface.